2013
DOI: 10.4102/phcfm.v5i1.456
|View full text |Cite
|
Sign up to set email alerts
|

Communities’ views, attitudes and recommendations on community-based education of undergraduate Health Sciences students in South Africa: A qualitative study

Abstract: BackgroundMedical and Health Sciences students in South Africa undertake community-based education (CBE). Health professionals based at host sites are jointly responsible for training of these students in conjunction with university staff. This study explored the communities’ views, attitudes and recommendations regarding CBE undertaken by these students, in order to improve the quality of community support for these programmes.MethodA qualitative descriptive study was conducted at CBE placement sites of stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…[11] This study showed that CBE could create learning opportunities for students to acquire these attributes. These findings were similar to those of Mabuza et al, [16] who indicated that the main focus of CBE was the learning of practical skills, professional behaviour and relating theory to practice. However, Ferris and O'Flynn [17] argue that for CBE to be more meaningful, students should not be left at these sites to acquire practical skills only; they should be given opportunities to self-reflect and self-assess, which can contribute to lifelong learning.…”
Section: Benefits To Institutionsupporting
confidence: 90%
“…[11] This study showed that CBE could create learning opportunities for students to acquire these attributes. These findings were similar to those of Mabuza et al, [16] who indicated that the main focus of CBE was the learning of practical skills, professional behaviour and relating theory to practice. However, Ferris and O'Flynn [17] argue that for CBE to be more meaningful, students should not be left at these sites to acquire practical skills only; they should be given opportunities to self-reflect and self-assess, which can contribute to lifelong learning.…”
Section: Benefits To Institutionsupporting
confidence: 90%
“…The results were in line with those of similar studies. (10) As the results showed, the main category of "preservation and promotion of health" had two sub-categories: "education" and "follow up and referral". In the provision of home care in remote areas, students played an important instructive role and the people benefited from the instruction provided by students and professors.…”
Section: Discussionmentioning
confidence: 99%
“…[8,[12][13][14] The main settings included in the studies were the university, the community, and the primary schools which were involved in the community-based programs.…”
Section: Discusion Of Findingsmentioning
confidence: 99%
“…Such preparation could help students, especially those without experience of rural life, to make the most of their placement opportunity. The evaluation of community programs [6,13,36] revealed a number of challenges which had similarities regardless of geographical location, participants, and political, socio-cultural and economic status.…”
Section: Theme 3: the Impact Of Community Nursing Education Programsmentioning
confidence: 99%
See 1 more Smart Citation